FINANCIAL FEASIBILITY ANALYSIS FOR DECISION-MAKING IN THE YODYA TOWER OFFICE BUILDING CONSTRUCTION PROJECT IN MAKASSAR - Yusmin, Yusmin; Onaning, Kamaruzzaman (UTSAHA: Journal of Entrepreneurship, 2025)
In the era of globalization and increasingly intense business competition, investment decision-making has become a key aspect of managing business operations efficiently and sustainably. Investing in office building construction is a strategic move that requires thorough planning and meticulous analysis. Poor investment decisions in such projects can have significant impacts on a company's financial stability and long-term viability. Therefore, the investment in the “Yodya Tower Office Building Construction Project in Makassar” necessitates a financial feasibility analysis based on capital budgeting methods, utilizing investment feasibility indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), Discounted Payback Period (DPP), and Payback Period (PP). Based on the financial feasibility calculations for the Yodya Tower Office Building Construction Project with an investment horizon of 20 years, the analysis yielded an NPV of IDR 15,737,034,946, an IRR of 9.73%, a PI of 1.15, a DPP of 18.4 years, and a PP of 11.9 years. According to these five investment parameters, the Yodya Tower Office Building Construction Project is considered financially feasible. Additionally, a sensitivity analysis was conducted to identify the variables that most significantly affect the investment feasibility indicators. This was further elaborated through three possible business scenarios: optimistic, normal, and pessimistic. The analysis revealed that an increase in construction costs is the most sensitive factor impacting the project's cash flow, leading to changes in NPV and other feasibility indicators. Furthermore, the capital structure analysis indicated that utilizing 30% equity and 70% debt financing would result in the most optimal NPV outcome.